NILAI NILAI PENDIDIKAN TAUHID DALAM KITAB AQIDATUL AWAM KARYA SAYYID AHMAD MARZUQI - Muhammad Iqbal Rosyada; Rosichin Mansur; Ibnu Jazari (VICRATINA, 2020)
Education is currently experiencing a decline in attitudes and behaviors that do not reflect faith in God. On the other hand they recognize that the religion they profess is the religion of Islam, but their attitudes and behavior do not reflect the religion itself. Many among the people of them often do things that are inappropriate. Among others: do dholim, dare to parents, getting drunk, gambling and so forth. All of that is due to lack of knowledge of the faith in themselves. Researchers chose the book of Aqidatul Awam by Sheikh al-Alim al-Allamah Sayyid Ahmad Marzuqi because this book discusses the unity of humanity in order to believe in God. So this book gives enthusiasm to know and study science as a way of life and can be applied to life. The formulation of the problem of this research is How is the content in the book of Aqidatul Awam by Sheikh al-Alim al-Allamah Sayyid Ahmad Marzuqi, how is the value of monotheism education in the book of Aqidatul Awam, and how are the implications of monotheism education in today's life. The research objectives Knowing the content in the book of Aqidatul Awam, Knowing the value of monotheism education in the book of Aqidatul Awam, and knowing the implications of monotheism education in today's life. This research uses a qualitative approach, this type of research is Library Research. The data source of this research is the book of Aqidatul Awam by Sheikh al-Alim al-Allamah Sayyid Ahmad Marzuqi as a primary data source, supported by secondary data, and tertiary data. Data collection techniques conducted by researchers with historical methods. This research data analysis method uses the content analysis method and the literature review method. The conclusions of the results of this study indicate that there are two grades of tahid education contained in the book of Aqidatul Awam, namely Divine values, and Insaniyah values. The Divine Value is related to the relationship of the servant with God, while the Insaniyah value is related to the relationship between humans and others.